Effect of Flaxseed Gum on the Microstructure and Physicochemical Properties of Starch in Frozen Dough - WANG Hongwei, LI Xiangjie, QIAO Jingyue, SHEN Huishan, ZHANG Yanyan, LIU Xingli, ZHAO Xuewei, ZHANG Hua (Shipin Kexue)
This study investigated the effects of adding different amounts of flaxseed gum (0%, 0.2%, 0.4%, 0.6% and 0.8%) on the microstructure and physicochemical properties of starch in frozen dough using scanning electron microscopy (SEM), solid-state nuclear magnetic resonance (SSNMR) spectroscopy, X-ray diffraction (XRD), and rapid visco analysis (RVA). The aim was to reveal the potential mechanism underlying the effect of flaxseed gum on the quality improvement of frozen dough from the perspective of changes in starch characteristics of frozen dough. The results showed that after repeated freeze-thaw cycles, the surface of starch particles appeared sunken, the relative crystallinity of starch decreased, the double helix structure of starch molecules was destroyed, and consequently water molecules were more likely to enter starch particles, thus resulting in an increase in peak viscosity and final viscosity. The addition of flaxseed gum inhibited the formation of ice crystals in frozen dough and delayed the unwinding of the double helix structure of starch molecules, and the hydrogen bond interaction between flaxseed gum and starch molecules increased the relative crystallinity of starch (22.2%–23.8%). As a result, the peak viscosity of starch decreased from 2 409.5 mPa⋅s to 2 247.2–2 288.5 mPa⋅s, and the gelatinization temperature gradually increased. In conclusion, flaxseed gum delayed the damage of starch in dough caused by repeated freeze-thaw cycles, thereby protecting frozen dough.